A New Multilocus Sequence Typing Scheme and Its Application for the Characterization of Photobacterium damselae subsp. damselae Associated with Mortality in Cetaceans - Alba, Patricia; Caprioli, Andrea; Cocumelli, Cristiano; Ianzano, Angela; Donati, Valentina; Scholl, Francesco; Sorbara, Luigi; Terracciano, Giuliana; Fichi, Gianluca; Di Nocera, Fabio; Franco, Alessia; Battisti, Antonio (Frontiers in Microbiology, 2016)
Photobacterium damselae subsp. damselae (PDD) is a known pathogen of fish, humans and marine mammals. In this study, a Multilocus Sequence Typing (MLST) scheme based on six housekeeping genes (glp, gyrB, metG, pnt, pyrC and toxR) was developed to better understand the PDD population structure and used to type 73 PDD isolates from cetaceans, mainly striped dolphins (Stenella coeruleoalba) involved in mortality episodes, and from a few marine chelonians. Five reference ATCC strains were also included in the study. Typing allowed the discrimination of groups of PDD strains isolated from different host species, at different times and from different geographic areas, suggesting that a clonal PDD group may have spread in the Tyrrhenian sea at the time of an Unusual Mortality Event (UME) among cetaceans, mainly striped dolphins, occurred in early 2013 along the Italian western coasts.